Biomaterials strategy for promoting palatal wound healing - Tong, Wen; Ren, Junxin; Yao, Xinyi; Wang, Siyi; Li, Wanhang; Zheng, Liyang; Hong, Xiaoxia; Zhao, Shufan (Frontiers in Bioengineering and Biotechnology, 2025)
Palatal wounds arising from trauma, tumors, cleft palate, or free gingival grafting (FGG) and other etiologies compromise critical orofacial functions including mastication, deglutition phonation and articulation, while posing life-threatening risks in severe conditions. Although surgical resection remains the primary clinical intervention, current treatment strategies for palatal injuries are constrained by several limitations, including: bacterial contamination and chronic inflammation, extensive soft tissue defects, postoperative scar formation, compromised blood supply in the surgical field, and potential patient comorbidities. Research on wound healing based on biomaterials has advanced substantially in recent decades, significantly facilitating their application in tissue engineering. This review provides a comprehensive overview of biomaterials used in palatal wounds, including acellular dermal matrix (ADM), platelet-rich derivatives (e.g., PRF, PRP), amniotic membrane, growth factor, hyaluronic acid, collagen, novel hydrogel, nanofiber scaffolds and other relevant materials. It further discusses potential mechanisms that may be involved in palatal wound healing. The objectives of this review are to summarize recent advances in preclinical and clinical studies on biomaterials for palatal wound healing and to highlight their therapeutic potential in this context.